Altruizm va «Niqoblangan egoizmʻning differensiatsiyаsi - Atabaeva, N.B (SCIENCE and SOCIETY, 2023)
This article analyzes the different and integral aspects of rational altruism from "disguised egoism" from a psychologi- cal point of view.
Keywords: altruism; rational altruism; "egoism in disguise"; behavior; motive; humanism